2023
DOI: 10.1080/24740527.2023.2266751
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Patient Education on Postoperative Pain, Opioid Use, and Psychological Outcomes: A Narrative Review

Rasheeda Darville-Beneby,
Anna M. Lomanowska,
Hai Chuan Yu
et al.

Abstract: Background Recent studies have shown that preoperative education can positively impact postoperative recovery, improving postoperative pain management and patient satisfaction. Gaps in preoperative education regarding postoperative pain and opioid use may lead to increased patient anxiety and persistent postoperative opioid use. Objectives The objective of this narrative review was to identify, examine, and summarize the available evidence on the use and effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Patients expressed concerns about understanding medication side effects and dependency risks, underscoring a gap in existing materials. This observation aligns with previous recommendations, emphasizing the importance of providing comprehensive, transparent, and accessible educational resources [26]. Such materials are essential for empowering patients to manage their pain following surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Patients expressed concerns about understanding medication side effects and dependency risks, underscoring a gap in existing materials. This observation aligns with previous recommendations, emphasizing the importance of providing comprehensive, transparent, and accessible educational resources [26]. Such materials are essential for empowering patients to manage their pain following surgery.…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, the increase of airway secretion caused by crying greatly increases the risk of anesthesia and the difficulty of airway management. In addition, preoperative anxiety is associated 6 with an increased incidence of postoperative delirium, anxiety-related postoperative behavioral changes, increased postoperative pain, and increased analgesic requirements [2,3]. These adverse effects may lead to delayed recovery and even postoperative complications, which may lead to increased economic and psychological burden on the patient's family.…”
Section: Introductionmentioning
confidence: 99%
“…A narrative review by Darville-Beneby et al was undertaken by a group of national chronic pain leaders who found that preoperative patient education interventions demonstrated promise with respect to improving postoperative outcomes. 6 This paves the way for the creation of a national preoperative education program which could be made available to all Canadians undergoing a surgical intervention.…”
mentioning
confidence: 99%